Physicochemical comparison of Wallacetrigona incisa (Sakagami & Inoue) and Tetragonula sapiens (Cockerell) honey from West Sulawesi: Perbandingan fisikokimia madu Wallacetrigona incisa (Sakagami & Inoue) dan Tetragonula sapiens (Cockerell) asal Sulawesi Barat - Phika Ainnadya Hasan; Hari Purwanto (Perhimpunan Entomologi Indonesia, 2026)
Wallacetrigona incisa (Sakagami & Inoue) and Tetragonula sapiens (Cockerell) are two stingless bee species widely cultivated for honey production in West Sulawesi, Indonesia. Yet, no comparative physicochemical data on their honey from this region exist. This study compared the physicochemical properties of W. incisa honey from a highland meliponary (1340 m a.s.l) and T. sapiens honey from a lowland meliponary (9 m a.s.l), and documented the flowering plant assemblages and abiotic conditions at each site. Ten parameters were assessed, including water content, ash, glucose, reducing sugar, fat, vitamins A and C, and antioxidant activity (IC50). W. incisa honey had higher water content (28.61%), glucose (61.18%), and vitamin C (374.61 µg/g) than T. sapiens (22.45%, 44.86%, 270.77 µg/g, respectively). T. sapiens honey had higher ash content (0.91% vs. 0.18%) and a higher IC50 value (562.81 vs. 423.40 ppm), indicating weaker antioxidant activity. These differences may be attributed to the contrasting altitudinal environments, including ambient humidity at the highland site (77.5% vs. 69.5% RH) and differences in surrounding vegetation (24 vs. 12 flowering plant species). W. incisa honey complied more closely with the Indonesian National Standards (SNI 8664:2024) threshold than T. sapiens honey. Further studies with replicated sampling are needed to confirm these preliminary findings.